Pessimistic View Of The Future Of Genetic Engineering In Veronica Roth's Divergent Trilogy Novel (2011-2013): A Sociological Approach - Larasati, Ajeng Sito, Dr. M. Thoyibi, M.S, Nur Hidayat, M. Pd (2016)
This study is about Pessimistic View of the Future of Genetic Engineering in Veronica Roth's Divergent Trilogy Novel (2011-2013), which is analyzed by using Sociological approach. The objectives of the study are to identify the characteristics of Pessimistic View of the Future of Genetic Engineering, to depict how Pessimistic View of the Future of Genetic Engineering, to reveal why Veronica Roth give concern in futuristic issues. This research belongs to qualitative research. The primary data of this research is Divergent Trilogy by Veronica Roth, while the secondary data of this research is other sources related to the study, such as: virtual sources and other printed materials that support this research. The researcher draws three conclusions in this research. First, the Pessimistic View of the Future of Genetic Engineering is characterized by such qualities as negative perception, anxiety, sadness, despair, doubtfulness, and low self-esteem. Second, the Pessimistic View of the Future of Genetic Engineering is depicted mainly through the plot illustrating that society cannot develop naturally, society wants equal treatment between genetic damage and genetic pure, society commit revenge to the bureau, and genetic damage is always accused of war, rebellion, or the kind of bad action. Third, the underlying reason of the author to give concern in futuristic issues is that the author wants to raise the awareness of the need for wise usage of science and technology, especially genetic engineering.